IMPLEMENTASI PEMBELAJARAN IPAS PADA KURIKULUM MERDEKA KELAS IV SD NEGERI GUGUS 3 KECAMATAN PENGASIH - Rantiyem, Deti; Musyadad, Faridl; Evitasari, Atika Dwi (Sindoro: Cendikia Pendidikan, 2024)
This study aims to examine the implementation, challenges, and efforts in teaching Science and Social Studies (IPAS) within the Merdeka Curriculum in Grade IV of public elementary schools in Cluster 3, Pengasih District. This research employs a qualitative approach using observation, interviews, and documentation techniques. The results show that the schools in Cluster 3, Pengasih District, have implemented the Merdeka Curriculum by providing autonomy to students and teachers in the learning process. The teachers have undergone various training programs, including workshops, technical guidance, and webinars, to support the curriculum implementation. The implementation process includes the stages of planning, execution, and evaluation. Lesson planning involves designing teaching modules tailored to students' characteristics and utilizing various learning resources, including digital media. The teaching execution includes preliminary activities, core activities, and closing activities. The evaluation phase comprises diagnostic, formative, and summative assessments. Challenges encountered include difficulties faced by students in understanding science materials that require deep reasoning and are filled with numerous unfamiliar terms, which makes them feel overwhelmed. The complexity of reasoning and understanding foreign terms in science materials poses significant obstacles. Additionally, the lack of infrastructure hinders the development of process skills, making learning media and teaching materials less effective. There is also limited real-life application relevant to the learning materials. Efforts to overcome these challenges include conducting routine evaluations to assess students’ understanding, discussing difficult topics, reteaching, and enriching learning resources. Efforts to address infrastructure shortages involve assessing needs, providing appropriate facilities, and fostering students' responsibility to maintain these facilities. Teachers take the initiative to independently provide learning media to ensure the availability of tools and to aid students in understanding the material. The application of scientific concepts is enriched by utilizing the internet, other books, or collaboration with other teachers to broaden students’ horizons. Penelitian ini bertujuan untuk mengetahui implementasi, kendala, dan upaya pembelajaran IPAS pada Kurikulum Merdeka di kelas IV SD Negeri Gugus 3 Kecamatan Pengasih. Penelitian ini merupakan penelitian kualitatif yang dilakukan dengan teknik observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa SD Negeri Gugus 3 Kecamatan Pengasih telah menerapkan Kurikulum Merdeka dengan memberikan kebebasan kepada peserta didik dan guru dalam proses pembelajaran. Guru-guru di sekolah tersebut telah dilatih melalui berbagai pelatihan, termasuk kombel, bimtek, dan webinar untuk mendukung penerapan kurikulum. Proses implementasi meliputi tahapan perencanaan, pelaksanaan, dan evaluasi. Perencanaan pembelajaran dilakukan dengan menyusun modul ajar yang sesuai dengan karakteristik peserta didik, dan menggunakan berbagai sumber belajar, termasuk media digital. Pelaksanaan pembelajaran dengan tahap kegiatan pendahuluan, kegiatan inti, dan kegiatan penutup. Pada tahap evaluasi mencakup assessment diagnostic, assessment formatif dan sumatif. Adapun kendala yang dihadapi, peserta didik mengalami kesulitan dalam memahami materi IPA yang memerlukan penalaran mendalam serta banyak istilah asing, yang mengakibatkan mereka merasa terbebani. Materi IPA yang memerlukan penalaran dan pemahaman, dan memahami istilah asing. Kurangnya sarana dan prasarana menyebabkan keterampilan proses sulit berkembang, media pembelajaran serta bahan ajar menjadi kurang efektif. Pada aplikasi ilmiah terbatasnya situasi nyata yang relevan dengan materi pembelajaran. Adapun Upaya untuk mengatasi kendala tersebut yaitu dengan evaluasi rutin dilakukan untuk menilai pemahaman peserta didik, mendiskusikan materi yang sulit, melakukan pengajaran ulang, dan menambah sumber belajar. Pemenuhan sarana dan prasarana melalui pendataan kebutuhan, penyediaan yang sesuai, serta membangun tanggung jawab peserta didik untuk menjaga fasilitas. Guru inisiatif menyediakan media pembelajaran secara mandiri guna memastikan alat bantu tersedia dan membantu peserta didik memahami materi. Aplikasi ilmiah diperkaya dengan memanfaatkan internet, buku lain, atau kerja sama dengan guru lain untuk memperluas wawasan peserta didik.